Immunoglobulin G Lymphocytotoxic Antibodies in Clinical Liver Transplantation: Studies Toward Further Defining Their Significance - Manez, Rafael (1995)
Twenty-two consecutive liver allograft recipients, who tested positive for immunoglobulin G (IgG) lymphocytotoxicity were subjected to pretransplantion and posttransplantation immunologic monitoring of antidonor IgG lymphocytotoxic antibody titers, total hemolytic complement activity (CH(100)), circulating immune complexes (CIC), and platelet counts in an effort to improve our understanding of the preformed antibody state in clinical hepatic transplantation. Ten contemporaneous liver transplant recipients whose crossmatch results were negative and who experienced severe hepatocellular damage early after transplantation were included as controls. Crossmatch test results were negative 1 day after transplantation and during the 1 month follow-up remained negative in 14 of 22 (64%) sensitized recipients, most of whom had relatively low (≤ 1:16) antidonor IgG antibody titers before transplantation. After transplantation, this group and the control group experienced no thrombocytopenia, no increase of CIC, and a gradual increase in CH(100) activity that reached normal levels within 1 week. A strong negative correlation between prothrombin time (PT) and CH(100) activity in these groups of patients suggested that changes in CH(100) activity (P < .0005) were tightly linked to liver synthetic function. In contrast, the crossmatch test results remained positive after transplantation in 8 of 22 (36%) sensitized recipients, all of whom had relatively high (>1:32 to 1024) pretransplantation titers of anti-donor IgG antibodies. After transplantation these patients developed a syndrome that was characterized by decreased CH(100) activity and increased CIC compared with pretransplantation levels and refractory thrombocytopenia that was associated with a 50% allograft failure rate because of biopsy-proven humoral and acute (cellular) rejection. Moreover, the lack of a strong negative correlation between PT and CH(100) activity (P = .1) in this group of patients suggested that the hypocomplementemia was not tightly linked to liver synthetic function. Before transplantation, determination of anti-donor antibody class (IgG) and titer alone showed a strong negative predictive value (100%) but less than optimal positive predictive value (67%) for identifying patients who experienced the posttransplantation syndrome described above. Therefore, evaluation of platelet counts, CH(100) activity, CIC, persistence of anti-donor antibodies and results of a liver biopsy performed after transplantation assisted in identifying sensitized liver allograft recipients who suffered the adverse consequences of the preformed antibody state.